EDUKASI DAN DETEKSI DINI TUMBUH KEMBANG ANAK USIA PRA SEKOLAH DI TK CILUUK BA MAKASSAR (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Growth and development are two interrelated processes with distinct characteristics. Child’s growth and development result from a complex interaction of various internal and external factors. Early detection and stimulation of child growth and development is an early monitoring effort to identifying developmental deviations in child in order to determine appropriate interventions that may influence their growth and development. Child’s growth is quantitative in nature and can be measured using anthropometric indicators, body weight, height, and head circumference. Child’s development is qualitative, reflected through changes in function and abilities in motoric skill, language, emotional, and social domains. Chronic nutritional problems indicate a close association with developmental delays in child. These conditions may be influenced factors from the prenatal period, infancy, early childhood (under five years old), to the preschool period. The method used in this activity is providing materials, conducting anthropometric measurements including height and weight. The results of anthropometric measurements carried out on 42 children at Ciluuk Ba Kindergarten Makassar, there were 7 children who were malnourished, there were 30 children who were well-nourished, there were 3 children who were over-nourished, there was 1 child who was obese, and there was 1 child who was malnourished.   ---   Pertumbuhan dan perkembangan merupakan dua peristiwa yang saling berhubungan, namun memiliki karakteristik yang berbeda. Tumbuh kembang anak merupakan hasil interaksi kompleks dari berbagai faktor internal dan eksternal. Stimulasi Deteksi Dini Tumbuh Kembang (SDIDTK) merupakan upaya pemantauan dini guna mengetahui penyimpangan anak guna menentukan intervensi yang dapat memengaruhi tumbuh kembang anak. Pertumbuhan anak bersifat kualitatif dan dapat diukur menggunakan antropometri meliputi berat badan, tinggi badan, dan lingkar kepala sebagai indikator fisik. Sedangkan, perkembangan bersifat kualitatif melalui perubahan fungsi dan kemampuan motorik, bahasa, emosional, serta sosial. Masalah gizi kronis mengindikasikan erat adanya keterlambatan perkembangan pada anak. Hal ini dipengaruhi dari masa prenatal, masa bayi, masa anak usia di bawah 5 tahun (balita) hingga prasekolah. Kegiatan pengabdian ini bertujuan untuk mengukur pertumbuhan anak prasekolah menggunakan alat antropometri dalam upaya deteksi dini pada anak. Sasaran kegiatan ini adalah anak di TK Ciluuk Ba Makassar. Metode yang digunakan adalah pemberian materi dan pengukuran antropometri meliputi berat badan dan tinggi badan. Hasil pengukuran antropometri pada 42 orang anak TK Ciluuk Ba Makassar menunjukkan variasi sebanyak 30 anak mengalami gizi baik, 7 anak mengalami gizi kurang, 3 anak mengalami gizi lebih, 1 anak mengalami obesitas, dan 1 anak mengalami gizi buruk.
Keywords: Growth; anthropometry; early detection; children; nutrition